2020
DOI: 10.3389/fimmu.2020.591741
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis in Lymph Nodes Is a Critical Regulator of Immune Response and Lymphoma Growth

Abstract: Tumor-induced remodeling of the microenvironment in lymph nodes (LNs) includes the formation of blood vessels, which goes beyond the regulation of metabolism, and shaping a survival niche for tumor cells. In contrast to solid tumors, which primarily rely on neo-angiogenesis, hematopoietic malignancies usually grow within pre-vascularized autochthonous niches in secondary lymphatic organs or the bone marrow. The mechanisms of vascular remodeling in expanding LNs during infection-induced responses have been stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 358 publications
(403 reference statements)
1
19
0
Order By: Relevance
“…In line, we found a strong reduction and even entire loss of HEVs in DLBCL and BL, a finding that was in strong contrast to largely intact HEVs in cHL. Different from the two aggressive B-NHL entities, cHL harbors only a minority of tumor-defining Hodgkin-Reed-Sternberg (HRS) cells, surrounded by a predominant benign immune cell infiltrate ( Menzel et al., 2020 ). Data showed that HRS-derived LTα activates ECs to enhance naive T cell recruitment by upregulating adhesion molecules and the ECM component hyaluronan ( Fhu et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In line, we found a strong reduction and even entire loss of HEVs in DLBCL and BL, a finding that was in strong contrast to largely intact HEVs in cHL. Different from the two aggressive B-NHL entities, cHL harbors only a minority of tumor-defining Hodgkin-Reed-Sternberg (HRS) cells, surrounded by a predominant benign immune cell infiltrate ( Menzel et al., 2020 ). Data showed that HRS-derived LTα activates ECs to enhance naive T cell recruitment by upregulating adhesion molecules and the ECM component hyaluronan ( Fhu et al., 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite their origin as autochthonous LN tumors, very little is known about the fate of HEVs in the context of B cell lymphoma (BCL). An important blood vessel pathology is the angiogenic increase of the microvessel density (MVD) ( Cardesa-Salzmann et al., 2011 ; Gloger et al., 2020 ; Menzel et al., 2020 ), which is prognostically unfavorable in diffuse large BCL (DLBCL). A previous immunohistology study found reduced numbers of HEVs with a damaged appearance in high-grade B cell non-Hodgkin lymphoma (B-NHL), while in low-grade tumors, HEVs were preserved ( Pajor et al., 1990 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…New vessels in tumor tissues are lifelines for the development of tumor cells. Through continuous angiogenesis, nutrients are continuously supplied and, at the same time, provide vascular channels for the distant local invasion and metastasis of tumor cells (14)(15)(16). Therefore, continuous angiogenesis ensures the continuation of the biological behaviors of tumors (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Through continuous angiogenesis, nutrients are continuously supplied and, at the same time, provide vascular channels for the distant local invasion and metastasis of tumor cells (14)(15)(16). Therefore, continuous angiogenesis ensures the continuation of the biological behaviors of tumors (15,16). Tumor angiogenesis (TA) also plays an essential role in tumors, especially in the malignant tumor system.…”
Section: Introductionmentioning
confidence: 99%